2019
DOI: 10.3114/fuse.2019.03.06
|View full text |Cite
|
Sign up to set email alerts
|

New and Interesting Fungi. 2

Abstract: One order, seven families, 28 new genera, 72 new species, 13 new combinations, four epitypes, and 21 interesting new host and / or geographical records are introduced in this study. Pseudorobillardaceae is introduced for Pseudorobillarda (based on P. phragmitis). New genera include: Jeremyomyces (based on J. labinae) on twigs of Salix alba (Germany); Neodothidotthia (based on N. negundinicola) on Acer negundo (Ukraine); Neomedicopsis (based on N. prunicola) on fallen twigs of Prunus padus (Ukraine); Neophaeoap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 80 publications
0
99
0
Order By: Relevance
“…Notes -Parafenestella was recently treated (Jaklitsch et al 2018, Valenzuela-Lopez et al 2018, Crous et al 2019b, and shown to have phoma-like asexual morphs. Within the genus Parafenestella, P. pittospori is phylogenetically distinct from other species known from DNA sequence data.…”
Section: Parafenestella Pittosporimentioning
confidence: 99%
“…Notes -Parafenestella was recently treated (Jaklitsch et al 2018, Valenzuela-Lopez et al 2018, Crous et al 2019b, and shown to have phoma-like asexual morphs. Within the genus Parafenestella, P. pittospori is phylogenetically distinct from other species known from DNA sequence data.…”
Section: Parafenestella Pittosporimentioning
confidence: 99%
“…The phylogenetic tree inferred from maximum likelihood (Figure 3) showed our isolate within a monophyletic clade (BPP 0.99/ BT 93%) comprising mostly of waterborne species, i.e., E. opportunistica, E. lacus, E. cancerae, E. psychrophila, E. salmonis, E. aquamarina, E. pisciphila (7) and other species originally isolated from non-aquatic sources, i.e., E. bonariae (22) and E. equina (7). Within the clade, it is closest to E. cancerae with high support (BPP 1.00 / BT 86%).…”
Section: Post-mortem Diagnosticsmentioning
confidence: 99%
“…Recently, a taxonomic key for the genus Caliciopsis has been presented (Garrido-Benavent and Perez-Ortega 2015). Caliciopsis nigra [now recombined to Hypsotheca nigra (Crous et al 2019)] is the causal agent of cankers on stems of the Mediterranean cypress, Cupressus sempervirens and common juniper, Juniperus communis (Intini 1980) and C. indica is a pathogen on Garcinia indica leaves (Pratibha et al 2010). Caliciopsis arceuthobii infects the flowers of several species of dwarf mistletoe in the genus Arceuthobium (Ramsfield et al 2009), Caliciopsis rhoina is associated with bark and trunk cankers on Toona sinensis (Rikkinen 2000), while Caliciopsis brevipes was reported on needles and bark of Araucaria araucana and C. cochlearia on needles and twigs of A. araucana, Fitzroya cupressoides, Austrocedrus chilensis, Pilgerodendron uviferum and Podocarpus nubigenus (Butin 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Caliciopsis arceuthobii infects the flowers of several species of dwarf mistletoe in the genus Arceuthobium (Ramsfield et al 2009), Caliciopsis rhoina is associated with bark and trunk cankers on Toona sinensis (Rikkinen 2000), while Caliciopsis brevipes was reported on needles and bark of Araucaria araucana and C. cochlearia on needles and twigs of A. araucana, Fitzroya cupressoides, Austrocedrus chilensis, Pilgerodendron uviferum and Podocarpus nubigenus (Butin 1970). More recently, Caliciopsis pleomorpha [now recombined in Hypsotheca as H. pleomorpha (Crous et al 2019)] has been reported as the causal agent of a canker disease on various Eucalyptus species in Australia (Pascoe et al 2018).…”
Section: Introductionmentioning
confidence: 99%